Penerapan Terapi Dzikir Terhadap Perubahan Skala Nyeri Post Operasi Di Ruang Mawar RSUD dr. Soehadi Prijonegoro Sragen - Liski Andari Noskivianti; Ika Silvitasari; Waluyo Waluyo (STIKes Ibnu Sina Ajibarang, 2023)
Background; The problem in postoperative patients is the pain felt due to surgical wounds. This results in patients feeling uncomfortable, uneasy, and various other emotional disturbances. So it is necessary to do dzikir therapy to treat pain. Purpose; Describe the effect of dhikr therapy on changes in postoperative pain scale. Method; Using a descriptive method in the form of a case study the two respondents focused on the implementation of dzikir therapy to reduce postoperative pain by giving dhikr therapy once for 3 days. Results; Dzikir therapy has an effect on changes in the postoperative pain scale so that the acute pain experienced by patients can be reduced. Patient 1 from a pain scale of 6 becomes a pain scale of 3 and Patient 2 from a pain scale of 6 becomes a pain scale of 2. Conclusion; Dzikir therapy in postoperative patients with pain can effectively reduce surgical pain and can be developed for further research